Patient and public involvement in basic and clinical psychiatric research: a scoping review of reviews - Werner, Anne; Lauberger, Julia; Steckelberg, Anke; Meyer, Gabriele (BMC psychiatry, 2025)
Background Patient and public involvement (PPI) in health research has become established as an essential component of international health research. Particularly, patients and stakeholders’ commitment to psychiatric research faces various challenges. This scoping review aimed to examine the existing literature to identify the aims, methods, barriers, and facilitators of PPI in clinical and basic psychiatric research. Methods This scoping review’s methods were guided by the framework proposed by Arksey and O’Malley. The literature search was conducted between October and November 2023 on six databases (MEDLINE, Web of Science, EMBASE, PsycInfo, PubPsych, and the Cochrane Library). We included reviews that summarized the results of primary studies describing methods for PPI in psychiatric scientific research, regardless of their subjects’ underlying psychiatric conditions and the primary research context (clinical or preclinical). The inclusion criteria included a description of the methods, components, and characteristics of participation in psychiatric research. We included reviews published between 2008 and 2023 regardless of participants’ language, country, or age. Findings Twenty reviews comprising 429 studies were included. They revealed that PPI was used to pursue various objectives (e.g., prioritizing research questions). Common methods included focus groups, advisory boards, workshops and interviews. Only one review reported financial compensation for those involved. PPI ranged from tokenism to involvement in data analysis and the dissemination of findings. Facilitators and barriers were identified in relationship and communication factors, organizational and practical factors, and in (co-) researchers training. The most frequently mentioned facilitators of successful PPI were trust and strong relationships. The most frequently mentioned barrier was the power imbalance between the participants and researchers. We identified positive and potential negative effects of PPI. Conclusion Golden rules for practice (clinical and basic research) derived from the results are as follows: (I) Foster a culture of collaboration and mutual respect between researchers and PPI participants. (II) Provide adequate resources and support for PPI activities, including funding and training programs. (III) Develop clear guidelines and standards for PPI to ensure consistency and quality. (IV) Develop a willingness to integrate PPI into all phases of research, from planning to the dissemination of results. Scoping review registration https://doi.org/10.17605/OSF.IO/7YS5C .